Occurrence of post weaning multisystemic wasting syndrome in crossbred pigs of Uttar Pradesh and Uttarakhand, India - RAJKHOWA, T K; SAIKUMAR, G (The Indian Journal of Animal Sciences, 2012)
Post weaning multisystemic wasting syndrome (PMWS) was first recognized in Canada in 1996 as a new emerging disease which caused wasting in post weaned pigs. Since then, PMWS has been recognized globally during the last decade. The present study was carried out to study occurrence of PMWS in pigs of organized pig farms in northern states of India i.e. Uttar Pradesh and Uttarakhand. A total 234 pigs out of 798 pigs in the age group of 5–12 weeks from a swine population of 1,298 were clinically examined over a period of 1 year. Thorough postmortem examination was carried out in 18 dead piglets and in 16 terminally ill piglets exhibiting clinical signs of PMWS, which were euthanized. Histopathology followed by immunohistochemistry and in situ hybridization with PCR techniques were used for diagnosis of the disease. This study is reporting high prevalence of PMWS in crossbred pigs of organized pig farms in Uttar Pradesh and Uttarakhand of India.